Iowa RBA, January 12, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Notes for the Iowa RBA for January 12, 1998. Highlights include Lesser Black-backed Gull, Glaucous Gull, and Thayer's Gull. Epson - sheet feed/flatbed